The Effects of Mechanical Stretch on Integrins and Filopodial-Associated Proteins in Normal and Glaucomatous Trabecular Meshwork Cells - Yang, Yong-Feng; Sun, Ying Ying; Peters, Donna M.; Keller, Kate E. (Frontiers in Cell and Developmental Biology, 2022)
The trabecular meshwork (TM) is the tissue responsible for regulating aqueous humor fluid egress from the anterior eye. If drainage is impaired, intraocular pressure (IOP) becomes elevated, which is a primary risk factor for primary open angle glaucoma. TM cells sense elevated IOP via changes in their biomechanical environment. Filopodia cellular protrusions and integrin transmembrane proteins may play roles in detecting IOP elevation, yet this has not been studied in detail in the TM. Here, we investigate integrins and filopodial proteins, such as myosin-X (Myo10), in response to mechanical stretch, an in vitro technique that produces mechanical alterations mimicking elevated IOP. Pull-down assays showed Myo10 binding to α5, αvβ3, and αvβ5 integrins, but not β1 integrin. Several of these integrins colocalized in nascent adhesions in the filopodial tip and shaft. Using conformation-specific antibodies, we found that β1 integrin, but not α5 or αvβ3 integrins, were activated following 1-hour mechanical stretch. Cadherin -11 (CDH11), a cell adhesion molecule, did not bind to Myo10, but was associated with filopodia. Interestingly, CDH11 was down-regulated on the TM cell surface following 1-hour mechanical stretch. In glaucoma cells, CDH11 protein levels were increased. Finally, mechanical stretch caused a small, yet significant increase in Myo10 protein levels in glaucoma cells, but did not affect cellular communication of fluorescent vesicles via filopodia-like tunneling nanotubes. Together, these data suggest that TM cell adhesion proteins, β1 integrin and CDH11, have relatively rapid responses to mechanical stretch, which suggests a central role in sensing changes in IOP elevation in situ.